Pelatihan Mekanik Sepeda Motor Untuk Anak Putus Sekolah Di Kelurahan Labuhbaru Barat Kecamatan Payung Sekaki Pekanbaru - Jusnita - Jusnita; Indra Hasan; Fikry Hadi (Jurnal Pengabdian UntukMu NegeRI, 2018)
Motorcycle Mechanic Training For Children Without SchoolIn West Labuhbaru Urban District Payung Sekaki Pekanbaru Jusnita1), Indra Hasan2) Fikri Hadi3) jusnita@umri.ac.id Abstract Needs service for motorcycles become a routine need to be done by users. The purpose of this activity is to provide training courses for workshop and training of automotive mechanics and to grow the entrepreneurship spirit, helping government program in overcoming unemployment. The methods used are lectures, questions, discussions, demonstrations and practice exercises. The benefits of this service are; The participants get the knowledge and mechanical skills otmotif, Lecturer can implement one tri Dharma Higher Education, for the local government the formation of qualified candidates. This activity was held in West Labuhbaru Village, Payung Sekaki Sub-district, followed by 15 participants, 1 elementary school graduate, 7 junior high school graduates and 7 senior high school graduates. This activity begins by gathering participants in the West Labuhbaru Village hall as a training ground. The results of community service activities in outline include the following components; 1). The success of the target number of trainees. 2) Achievement of training objectives 3) Achievement of material targets that have been planned 4). The ability of participants in the mastery of the material. Target trainees as planned before 10 people. In the implementation, this activity was attended by 15 participants. Thus it can be said that the target participants reached 100%. The figures indicate that the community service activities seen from the number of participants who follow can be said successful / successful. Keywords: Training, Workshop, Training, Automotive, Entrepreneurship